Analisis Pengelolaan Arsip di Kantor Kecamatan Bungah Kabupaten Gresik - Muhammad Rifat Basya; Durinda Puspasari (Universitas Negeri Surabaya, 2021)
This research aims to analyze: 1) records management at the Bungah sub-district office of the Gresik district; 2) obstacles in managing records at the Bungah sub-district office of the Gresik district; 3) efforts to overcome archival management barriers at the Bungah sub-district office of the Gresik district. This type of research used in this research is descriptive research with a qualitative approach. The subjects of this study were 3 administrative staff at the Bungah district office in Gresik regency. Data collection techniques used by researchers are interviews. The data analysis technique used by researchers is data analysis in the Miles and Huberman field models and using source triangulation. The results obtained show that: 1) the implementation of records management in the Bungah sub-district office of the Gresik district is still inadequate and not systematic; 2) obstacles in managing archives at the Bungah sub-district office of the Gresik district, among others: lack of archive storage facilities, accumulation of letters in storage, archive storage for a while still stored in cardboard boxes, and a lack of skilled personnel in managing archives; 3) efforts in overcoming archival management barriers by maximizing the storage facilities of existing equipment and equipment so that the stack of paper can be minimized as well as involving archival managers in archival training.